ANALISIS PENGARUH KEPEMILIKAN INSTITUSIONAL, KOMISARIS INDEPENDEN, LEVERAGE, UKURAN PERUSAHAAN DAN PROFITABITAS TERHADAP TAX AVOIDANCE (Studi Empiris pada Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia tahun 2014-2018) - Widaryanti, Widaryanti (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
This study aims to obtain empirical evidence on the effect of institutional ownership, independent commissioners, leverage, firm size and profitability on tax avoidance. This  esearch is focused on the Consumer Goods Industry Listed on the Indonesia Stock Exchange in 2014-2018. The observations in this study were as many as 85 samples. Research obtained by  on probability sampling method, namely purposive sampling technique. The technique used in  his research is multiple linear regression analysis. The results of this analysis indicate that  everage and firm size have an effect on tax avoidance, but institusional ownership, independent  ommissioners and profitability have no effect on tax avoidance.Keywords: Institutional Ownership, Independent Commissioner, Leverage, Firm Size, Profitability, Tax Avoidance.